Productivity and Environmental Friendliness Evaluation of Circular Net Fishing Gear in West Java - Rita Rostika; Lantun Paraditha Dewanthy; Alexander M. Khan (International Journal Labs, 2023)
Based on the mission of the Ministry of Marine Affairs and Fisheries (MMAF), namely about sustainability where one of the focuses of realization efforts carried out is to improve the sustainability of capture and aquaculture businesses. The potential of ??ng waters can be developed including ?d?l?h d? freshwater waters (rivers, lakes, ponds), brackish waters (ponds) and marine waters (beaches and high seas). The noble mission is also outlined in the implementation of the 6th nawacita, namely fisheries resource management directed through sub-agendas: Acceleration of national economic growth through increasing fishery products, namely through improving the quality, added value and innovation of fisheries technology, improving the quality of fishery facilities and infrastructure, improving fisheries governance and sustainable fisheries management. This study aims to analyze the diversity of the types of circular net fishing equipment in West Java Province, especially the marine waters of the North West Java region, the productivity value of ring nets based on the type and classification of fishing vessel sizes authorized by the Provincial Government, and productivity and level of environmental friendliness of ring nets used in West Java Province, especially the sea waters of the northern region of West Java. The study areas studied were the northern coastal areas in West Java, namely Bekasi Regency, Karawang Regency, Subang Regency, Indramayu Regency, and Cirebon Regency. This activity was carried out for one month, namely July 2022.